Logging evaluation of shale oil in the second member of Funing Formation of Qintong Sag, Subei Basin - WANG Xin,HAN Jianqiang,ZAN Ling,LI Xiaolong,PENG Xingping (Youqicang pingjia yu kaifa)
The efficient evaluation of the oil properties, capabilities, and compressibility of reservoirs using conventional logging data is essential for the large-scale development of shale oil in northern Jiangsu. Utilizing conventional logging data alongside core experiment data, this study develops a robust model to calculate several critical reservoir characteristics. These include total organic carbon content, effective porosity, bedding fracture density, and mineral composition content. The model employs a variety of mathematical methodologies such as physical concept analysis, optimization, fitting, and both forward and backward numerical simulations. Furthermore, this research classifies the sedimentary structure and lithofacies of the reservoir. Results indicate that the shale within the second member of Funing Formation in Qintong Sag predominantly consists of organic-rich layered/laminated mudstone and block mudstone. Among these, the layered or laminated mudstone represents the favorable lithofacies, intersecting vertically with non-favorable rock types. The “sweet spot” layers identified by the model correlate well with the layers analyzed using specialized logging techniques, and field applications have yielded positive outcomes. This technology has been successfully applied in identifying geological and engineering “sweet spots” within the shale oil reservoirs of the Subei Basin, offering significant guidance for the strategic development of shale oil in the region.